Postmenopausal Chinese women show accelerated lumbar disc degeneration compared with Chinese men - Wang, Yi Xiang J. (J Orthop Translat, 2015)
BACKGROUND/OBJECTIVE: Postmenopausal women may have accelerated disc degeneration due to relative oestrogen deficiency. Two new studies supporting this concept were carried out. METHODS: Study I: The data were from the Osteoporotic Fractures in Men (Hong Kong) and Women (Hong Kong) studies. Both were population-based studies on bone health for elderly Chinese men and women (age ≥ 65 years, n = 2000 for men and n = 2000 for women). Based on lumbar spine radiographs, changes in L1/2–L4/5 disc space height were classified into four categories: 0 = normal; 1 = mild narrowing (< 30% reduction in disc height); 2 = moderate narrowing (30–60% reduction in disc height); and 3 = severe narrowing (> 60% reduction in disc height). Sums of the disc space narrowing scores of each participant were plotted against their age. Study II: 12 healthy individuals and 53 persons who had mild nonspecific low back pain (30 males and 35 females; mean age, 53.4 years; age range, 23–76 years) were recruited. Magnetic resonance imaging was performed on a 3-T system. A multiecho turbo spin echo pulse sequence was used for lumbar disc T2 mapping. Regions of interest were manually drawn over nucleus pulposus on the T2 map of the discs. The means of T2 relaxation times of discs L1/2–L4/5 of the participants were plotted against their age. RESULTS: Study I: Elderly women had a higher disc space narrowing score than elderly men, and the slope of the plot was steeper for females than for males. When the plots were extrapolated to younger age, they intersected at 59.67 years. Study II: An age-related reduction of T2 value in the nucleus pulposus was demonstrated, which was faster in females than in males. Although females tended to have initial higher T2 value before 50 years, this trend was reversed in elderly persons, with an intersection at 52.4 years. CONCLUSION: Postmenopausal Chinese women show accelerated lumbar disc degeneration compared with Chinese men.